1991
DOI: 10.1111/j.1471-4159.1991.tb03444.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cortical [3H]Kainate and α‐[3H]Amino‐3‐Hydroxy‐5‐Methyl‐4‐Isoxazolepropionic Acid Binding in a Spontaneous Canine Model of Chronic Hepatic Encephalopathy

Abstract: Excitatory amino acid receptor binding parameters were investigated in a spontaneous dog model of chronic hepatic encephalopathy. L-[3H]Glutamate, (+)-[3H]-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-im ine maleate ([3H]MK-801), [3H]kainate, and alpha-[3H]-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid ([3H]AMPA) binding experiments were performed using crude cerebrocortical synaptosomal membrane preparations from dogs with congenital portosystemic encephalopathy (PSE) and control dogs. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 49 publications
0
14
1
1
Order By: Relevance
“…Thus, during experimental hepatic encephalopathy from acute liver failure there may be a selective loss of kainate receptors (Ferenci et al, 1984a), with a preservation of NMDA receptors (present study). Chronic hepatic encephalopathy appears to be associated with variable changes of the glutamate receptor populations (Peterson et al, 1990;Maddison et al, 1991). Conflicting results have also been found during hyperammonemia (Ferenci et al, 1984a;Rao et al, 1991;and present study).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Thus, during experimental hepatic encephalopathy from acute liver failure there may be a selective loss of kainate receptors (Ferenci et al, 1984a), with a preservation of NMDA receptors (present study). Chronic hepatic encephalopathy appears to be associated with variable changes of the glutamate receptor populations (Peterson et al, 1990;Maddison et al, 1991). Conflicting results have also been found during hyperammonemia (Ferenci et al, 1984a;Rao et al, 1991;and present study).…”
Section: Discussioncontrasting
confidence: 49%
“…However, in acute liver failure from hepatectomy and tetrachloride in the rat (Watanabe et al, 1988), thioacetamide in the rat (Zimmermann et al, 1989) and ischemic liver necrosis in the rabbit (present study) no changes were found, although in the latter we cannot exclude changes of the kainate and AMPA receptors. In rats with chronic hepatic encephalopathy glutamate binding to the NMDA receptor was diminished (Peterson et al, 1990); in dogs with chronic hepatic encephalopathy NMDA receptor binding appeared normal whereas changes occurred in the kainate and AMPA receptors (Maddison et al, 1991). No changes in glutamate receptors were found in models of acute hyperammonemia in rabbits (Ferenci et al, 1984a, present study).…”
Section: Discussionmentioning
confidence: 44%
“…Many different hepatotoxins, such as carbon tetrachloride, 20,21 thioacetamide, 22,23 nitrosamines, 24 halogenated anesthetics, 25,26 and murine hepatitis, 27,28 have been described in the literature. This review discusses two of the more widely used hepatotoxins, galactosamine [29][30][31][32][33][34][35][36] and acetaminophen.…”
Section: Chemical Modelsmentioning
confidence: 99%
“…[ 3 H]AMPA (NEN-Dupont, 46.1 Ci/mmol) binding assay was performed by means of a filtration assay essentially as described by Maddison et al [1991] using 50 g P2 fraction protein. Nonspecific binding was defined as the amount of radioactivity bound in the presence of 100 M unlabelled AMPA.…”
Section: Radioligand Binding Assaysmentioning
confidence: 99%